Arah Baru Perencanaan Pendidikan Dan Implikasinya Terhadap Kebijakan Pendidikan - Abdul Muis Daeng Pawero (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
Whether bad or qualified or poorly educated will be much influenced by the governance system. Educational governance systems will develop well when implemented through good systems by clean and professional managers. The system has been designed in detail by the government established through the number 19 of 2007 permendiknas on